Assessment of Aminoglycoside-Induced Hearing Loss Risk in the Perinatal Period - Thompson, Whitney S.; Saba, Leslie; Hasadsri, Linda; Girard, Sylvie; Schimmenti, Lisa A.; Bendel-Stenzel, Ellen M.; Wick, Myra J.; Brumbaugh, Jane E. (American Journal of Perinatology, 2024)
Objective This study aimed to determine the prevalence and heteroplasmy level(s) of MT-RNR1 variants m.1555A > G and m.1494C > T, which are associated with aminoglycoside-induced hearing loss, in a general perinatal population. This study also aimed to characterize the association of these variants and their heteroplasmy levels with hearing loss outcomes with and without aminoglycoside exposure.Study Design Droplet digital polymerase chain reaction was performed on 479 maternal DNA samples from a general perinatal biobank at our institution to detect the presence and heteroplasmy levels of MT-RNR1 variants m.1555A > G and m.1494C > T. Testing of paired neonatal specimen(s) was planned for positive maternal tests. A retrospective chart review was performed to characterize the population, identify aminoglycoside exposures, and determine hearing outcomes.Results All maternal samples tested negative for MT-RNR1 variants m.1555A > G and m.1494C > T. Maternal and neonatal subjects had high rates of aminoglycoside exposure (15.9 and 13.9%, respectively). No subjects with sensorineural or mixed hearing loss had documented aminoglycoside exposure.Conclusion This study demonstrated that a larger sample size is needed to establish the prevalence of these variants as no subjects tested positive. Determination of variant prevalence in the neonatal population, association of variant heteroplasmy levels with hearing outcomes, and reliability of maternal testing as a surrogate for neonatal testing are important next steps toward universal prenatal or newborn screening.Key Points
Keywords: mitochondrial genetics; hearing loss; aminoglycoside antibiotics; newborn screening